High-performance multifunctional cable and preparation method thereof

By introducing nickel-titanium wires and a multifunctional composite aerogel layer into the cable, combined with a phenolic resin/silica network and MXene nanosheets, the problem of integrating multiple performance characteristics of the cable under extreme environments was solved, achieving high reliability, intelligent operation, and long service life of the cable.

CN120854050AActive Publication Date: 2025-10-28BAODING JINGYANG LIJIN CABLE MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511375282.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-10-28
Estimated Expiration
2045-09-25

AI Technical Summary

Technical Problem

Existing high-performance cables struggle to achieve deep integration of multiple performance characteristics in extremely harsh environments, resulting in problems such as low thermal insulation efficiency, complex structure, poor flexibility, insufficient waterproofing and anti-icing capabilities, and low level of intelligence.

Method used

The design employs nickel-titanium wires and a multifunctional composite aerogel layer, achieving self-healing and active de-icing through shape memory alloy wires. The combination of phenolic resin/silica network framework and MXene nanosheets constructs an interpenetrating network structure, integrating sensing and response functions.

Benefits of technology

It achieves high reliability and long service life of cables in extreme environments, and has real-time health monitoring, active de-icing and self-repair capabilities, while simplifying the structure and reducing weight and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120854050A_ABST
    Figure CN120854050A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance multifunctional cable and a preparation method thereof, and belongs to the technical field of cables, and the preparation method comprises the following steps: 1, stretching a nickel-titanium wire to generate strain, coating the surface of the nickel-titanium wire with an insulating layer to obtain a shape memory alloy wire, and tightening and fixing the shape memory alloy wire in an inner cavity of a polytetrafluoroethylene mold; 2, mixing the phenolic resin prepolymer solution containing the thermochromic microcapsules, MXene / ethanol dispersion liquid and silicon dioxide sol to obtain mixed sol, adjusting the pH value of the mixed sol, and stirring to obtain multifunctional composite sol; 3, the multifunctional composite sol is injected into a polytetrafluoroethylene mold where a shape memory alloy wire is fixed, gelation and modification are conducted, and modified multifunctional composite gel is obtained; step 4, carrying out supercritical COdrying on the modified multifunctional composite gel to obtain multifunctional composite aerogel; and 5, filling the multifunctional composite aerogel between the conductor with the insulating layer and the cable sheath.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable technology, specifically relating to a high-performance multifunctional cable and its preparation method. Background Technology

[0002] With the rapid development of new energy, specialized industries, aerospace, and marine exploration, unprecedentedly high performance requirements have been placed on cables used in extremely harsh environments. These cables not only need to ensure stable power and signal transmission, but also require excellent comprehensive protection capabilities, including high-temperature resistance, flame retardancy, waterproofing and anti-icing properties, abrasion resistance, and chemical corrosion resistance, under multiple complex factors such as high temperature, open flame, humidity, icing, mechanical wear, and chemical corrosion. However, existing high-performance cables still face many insurmountable technical bottlenecks.

[0003] Currently, most technical solutions on the market addressing these needs employ traditional material layering and structural design approaches. Typical practices and inherent drawbacks include: In terms of heat insulation and flame retardancy, multi-layer wrapping with mica tape, fiberglass braided tape, or halogen-free flame-retardant tape (such as polyimide tape) is commonly used as the heat insulation and flame-retardant layer. While these materials offer some effectiveness, their relatively high thermal conductivity (typically > 0.05 W / (m·K)) limits their heat insulation efficiency. Under sustained high temperatures or open flame, the organic binder is prone to carbonization and failure, leading to structural collapse and difficulty in maintaining the integrity of the cable over a long period. Furthermore, multi-layer wrapping significantly increases the cable's diameter, weight, and rigidity, severely sacrificing its flexibility and ease of installation. Regarding waterproofing and anti-icing, physical waterproofing relies mainly on metal sheaths (such as lead sheaths or corrugated copper sheaths) or heavy polymer sheaths. Metal sheaths are bulky, costly, and prone to fatigue fracture, while heavy polymer sheaths reduce cable flexibility and are prone to embrittlement and cracking under dynamic bending and low-temperature environments, creating weak points in waterproofing. Anti-icing relies heavily on the low surface energy of the sheath material, a passive protection strategy. Ice can still adhere, requiring significant energy for external de-icing. In terms of mechanical properties and durability, cable structures are often designed with exceptional complexity to balance various performance requirements, resulting in numerous interfaces between layers. Under dynamic bending, torsion, and other mechanical stresses, mismatches in the thermal expansion coefficients and elastic moduli of different materials can easily lead to problems such as interface peeling and sheath wrinkling, affecting long-term reliability.

[0004] In recent years, aerogel, as a new type of nanoporous super thermal insulation material, has brought new hope for solving the above-mentioned thermal insulation problems due to its extremely low thermal conductivity (<0.025 W / (m·K)), lightweight, high specific surface area and excellent fire resistance. In the existing technology, there have been attempts to apply aerogel (mainly silica aerogel) to cables, for example, filling the gaps between the cable cores in the form of powder or particles, or preparing it into a felt-like body for wrapping. However, these applications have significant limitations: (1) The inherent brittleness of silica aerogel makes it very easy to pulverize and settle during cable laying and installation, especially in repeated dragging and bending in mobile situations, which leads to a sharp decline in thermal insulation performance and the formation of local hot spots, ultimately causing insulation failure and making it impossible to guarantee reliability. (2) It has a single function and requires passive protection. Traditional silicon-based aerogel has strong hydrophilicity. When it comes into contact with water, its nanoporous structure will collapse, and the thermal insulation performance will fail irreversibly. Moreover, the volume expansion may squeeze the internal conductor. Therefore, it not only cannot be waterproof, but also requires an additional waterproof layer to protect it, which increases the complexity and cost of the structure. (3) Insufficient integration and intelligence. Simple filling or wrapping is difficult to form an effective synergistic enhancement effect with other functional layers of the cable. It is merely a physical "addition" rather than a structural "fusion". More importantly, the existing aerogel application scheme has no sensing and response capabilities at all. It is a "dumb" material that cannot monitor the mechanical strain, local overheating and other health status of the cable in real time. It also cannot actively de-ice when icing or trigger an early warning when damaged. It cannot meet the needs of smart grids and modern industrial systems for the perception and interaction of equipment status.

[0005] Therefore, those skilled in the art have been dedicated to developing a truly multifunctional, integrated, high-performance cable. The core challenge lies in creating a new material that not only possesses ultra-lightweight, ultra-insulating, and highly flexible properties, but also deeply integrates with its inherent waterproofing, active de-icing capabilities, and intelligent sensing and early warning functions. This would fundamentally break through the traditional paradigm of "multi-layered stacking," "functional isolation," and "passive protection" in existing technologies, achieving the goal of high reliability, long lifespan, and intelligent operation of the cable under extreme conditions.

[0006] Therefore, designing a high-performance, multi-functional cable and its manufacturing method is in line with practical needs. Summary of the Invention

[0007] The purpose of this invention is to solve the problems existing in the above-mentioned background art by proposing a high-performance multifunctional cable and its preparation method.

[0008] A method for manufacturing a high-performance multifunctional cable includes the following steps: Step 1: Fix the nickel-titanium wire on the pre-stretching fixture and stretch it at a uniform speed until a strain of 4% is generated. After uniformly coating the surface with an insulating layer, a shape memory alloy wire is obtained. The processed shape memory alloy wire is then taut and fixed in the center of the inner cavity of the polytetrafluoroethylene mold. Step 2: Mix the phenolic resin prepolymer solution containing thermochromic microcapsules, MXene / ethanol dispersion, and silica sol at a mass ratio of 1:1:1 to obtain a mixed sol. Slowly add ammonia water to precisely adjust the pH value of the mixed sol to 7.5. After stirring, a multifunctional composite sol is obtained. Step 3: Inject the multifunctional composite sol into the polytetrafluoroethylene mold with the shape memory alloy wire fixed in place, seal the cover plate, and then perform gelation and modification to obtain the modified multifunctional composite gel. Step 4: The modified multifunctional composite gel is soaked in anhydrous ethanol and n-hexane in sequence to displace the modifier in the pores of the modified multifunctional composite gel itself, and then dried with supercritical CO2 to obtain multifunctional composite aerogel. Step 5: Fill the space between the insulating conductor and the cable sheath with multifunctional composite aerogel to form a multifunctional composite aerogel layer.

[0009] Preferably, in step one, the diameter of the nickel-titanium wire is 100μm, and the insulating layer is polyimide varnish. After the polyimide varnish is coated on the outer surface of the nickel-titanium wire, it is placed in an oven at 80°C for 1 hour to cure, and an insulating layer will be formed on the outer surface of the nickel-titanium wire.

[0010] Preferably, in step two, the preparation method of the phenolic resin prepolymer solution containing thermochromic microcapsules is as follows: resorcinol and formaldehyde are mixed in deionized water at a molar ratio of 1:2, and sodium carbonate is used as a catalyst to react at 60°C for 4 hours to obtain a phenolic resin prepolymer solution with a solid content of 20%. In the phenolic resin prepolymer solution, thermochromic microcapsules equivalent to 1 wt% of the solid mass of phenolic resin are added, and the mixture is stirred evenly to obtain a phenolic resin prepolymer solution containing thermochromic microcapsules.

[0011] Preferably, in step two, the thermochromic microcapsules consist of an oil phase mixture and an aqueous phase mixture. The oil phase mixture is prepared by heating and melting 5 wt% crystal violet lactone, 25 wt% bisphenol A or octadecylphosphonic acid, and 70 wt% tetradecyl alcohol or hexadecyl alcohol, or a mixture thereof, at 85°C, and stirring to form a homogeneous liquid oil phase mixture. The aqueous phase mixture is prepared by adding deionized water and 10 wt% water-soluble polymer to a beaker, stirring to dissolve and obtain an aqueous phase mixture. The oil phase mixture is then added to the aqueous phase mixture under shear at 10,000 rpm for 5-10 minutes to form a stable oil-in-water emulsion. The pH of the emulsion is adjusted to 3.5 using citric acid or sodium acetate solution. Within an acidic range of 4.5, 5 wt% melamine-formaldehyde prepolymer was slowly added. After stirring, the mixture was reacted at 60-70°C for 1 hour. The melamine-formaldehyde prepolymer gradually crosslinked and solidified, precipitating from the aqueous mixture and depositing on the surface of the oil phase droplets to form a transparent shell. The temperature was then gradually increased to 80-85°C, and the reaction continued for 1-2 hours until the shell was completely solidified and hardened. After the reaction was completed, the mixture was cooled to room temperature, and the microcapsule product was collected by filtration. It was repeatedly washed with deionized water and ethanol until the filtrate was neutral and clear. The microcapsule product was vacuum dried at 40°C to obtain a white thermochromic microcapsule powder.

[0012] Preferably, in step two, the preparation method of the MXene / ethanol dispersion is as follows: the MXene aqueous dispersion is filtered into a film by vacuum filtration, then redispersed in anhydrous ethanol, and ultrasonically treated by a probe to obtain a stable MXene / ethanol dispersion.

[0013] Preferably, in step two, the silica sol is prepared by mixing tetraethyl orthosilicate, anhydrous ethanol, and deionized water in a molar ratio of 1:4:4, adjusting the pH to 3.0 by adding HCl dropwise, and stirring at 40°C for 2 hours to obtain a clear silica sol.

[0014] Preferably, in step three, the gelation and modification process is as follows: the polytetrafluoroethylene mold containing the multifunctional composite sol is placed in a 60°C forced-air drying oven and left to stand for 6 hours to complete the gelation process, thereby obtaining a multifunctional composite wet gel. The multifunctional composite wet gel, together with the polytetrafluoroethylene mold, is then immersed in sufficient anhydrous ethanol and soaked at room temperature for 24 hours, during which the anhydrous ethanol is replaced 3 times to complete the aging process. Finally, the aged multifunctional composite wet gel is transferred to a perfluorodecyltriethoxysilane / ethanol solution and soaked at 50°C for 48 hours to complete the hydrophobic modification.

[0015] Preferably, in step four, the supercritical CO2 drying process is as follows: the modified multifunctional composite gel is placed in a supercritical drying vessel, liquid CO2 is introduced, and the temperature is maintained at 10℃ and 6 MPa for 2 hours. Then, the temperature is increased to 50℃ at 0.5℃ / min, and the pressure is increased to 12 MPa at 1 MPa / min. This condition is maintained for 3 hours. Finally, the pressure is released to atmospheric pressure at 50℃ at a rate of ≤0.1 MPa / min.

[0016] A high-performance multifunctional cable is prepared by a method for manufacturing a high-performance multifunctional cable.

[0017] The beneficial effects of this invention are: This invention represents a significant leap from passive protection to active sensing and response, greatly enhancing the intelligence and safety of cables. It successfully integrates a synergistic system composed of an MXene nanonetwork and shape memory alloy wires into a multifunctional composite aerogel, endowing the material with both "nerve" and "muscle" functions. This allows the cable to sense its strain (e.g., bending, compression) and temperature (e.g., localized overheating) changes in real time and in a distributed manner, and to monitor the cable's health status online via electrical signal output. In icing environments, it can actively activate efficient, low-energy electrothermal de-icing, transforming passive defense into proactive threat elimination. When microcracks appear due to fatigue, the shape memory alloy wires can provide driving force under overheating conditions, enabling self-repair of the cracks. This completely changes the traditional "dumb" and "passive" characteristics of cable aerogels, providing a revolutionary solution for the safe operation of critical lines. Through multi-scale structural design and composite synergy, this invention achieves both excellent mechanical properties and extreme environmental tolerance, resolving a long-standing performance contradiction. By constructing a phenolic resin / silica dual-network framework, introducing MXene two-dimensional nanosheet reinforcement, and in-situ fluorination modification, this invention solves the bottlenecks of mechanical properties and functionality of traditional aerogels at the molecular and microscopic levels. This allows the aerogel to maintain its core advantages of ultra-low density (~0.20 g / cm³) and ultra-low thermal conductivity (<0.023 W / m·K), while also possessing high flexibility (bendability), high compressive strength, and superhydrophobicity. This means that the cable, while possessing ultimate thermal insulation capabilities, has significantly improved resistance to mechanical damage and inherent, durable waterproof and anti-icing capabilities. This invention overcomes the technical difficulties of "thin and light cannot be strong and tough" and "thermal insulation cannot be waterproof" in traditional solutions, significantly extending the service life of the cable under complex working conditions. Highly integrated functionality simplifies cable structure and reduces overall system cost and energy consumption. This invention creatively integrates multiple functions such as heat insulation, flame retardancy, waterproofing, sensing, heating, and early warning into a single aerogel layer. This simplifies the design of multi-layered shielding structures in cables, avoiding the use of separate sensors, heating wires, and heavy waterproof metal sheaths. This reduces the overall weight and volume of the cable, improving the ease of installation and applicability. Furthermore, the electrothermal de-icing system based on MXene and shape memory alloy wires boasts high thermal efficiency, and the visual early warning mechanism (thermochromic) requires no external power supply. From a life-cycle perspective, this significantly reduces the operating and maintenance costs of the cable. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the cross-section of the high-performance multifunctional cable in this invention; Figure 2 This is a schematic diagram of the shape memory alloy wire in this invention; Figure 3 This is a flowchart illustrating the preparation process of the multifunctional composite aerogel in this invention. In the picture: 1: Shape memory alloy wire; 111: Nickel-titanium wire; 112: Insulation layer; 2: Phenolic resin prepolymer solution; 3: Thermochromic microcapsules; 4: MXene / ethanol dispersion; 5: Silica sol; 6: Ammonia water; 7: Multifunctional composite sol; 8: Polytetrafluoroethylene mold; 9: Modified multifunctional composite gel; 10: Anhydrous ethanol; 11: n-Hexane; 12: Multifunctional composite aerogel; 13: Cable; 131: Conductor; 132: Insulating outer layer; 133: Multifunctional composite aerogel layer; 134: Shielding layer; 135: Protective layer. Detailed Implementation

[0019] To better illustrate the preparation process involved in this invention and its advantages over the prior art, further explanation will be provided with reference to the accompanying drawings.

[0020] As shown in the attached figure, a method for manufacturing a high-performance multifunctional cable includes the following steps: Step 1: As Figure 2 As shown, the pretreatment of shape memory alloy wire 1 is as follows: nickel-titanium wire 111 is fixed on a pre-stretching fixture and stretched at a uniform speed until a strain of 4% is generated. After uniformly coating an insulating layer 112 on its surface, shape memory alloy wire 1 is obtained. The treated shape memory alloy wire 1 is tightened and fixed in the center of the inner cavity of the polytetrafluoroethylene mold 8. Step Two: As Figure 3As shown, a mixed sol is obtained by mixing phenolic resin prepolymer solution 2 containing thermochromic microcapsules 3, MXene / ethanol dispersion 4, and silica sol 5 in a mass ratio of 1:1:1. Ammonia water 6 with a volume fraction of 15%-28% is slowly added dropwise until the pH value of the mixed sol is precisely adjusted to 7.5. After gently stirring for 5 minutes, a multifunctional composite sol 7 is obtained. Step 3: Inject the multifunctional composite sol 7 into the polytetrafluoroethylene mold 8 in which the shape memory alloy wire 1 has been fixed, seal the cover plate, and after gelation and modification, obtain the modified multifunctional composite gel 9. Step 4: The modified multifunctional composite gel 9 is soaked in anhydrous ethanol 10 and n-hexane 11 for 12 hours each to completely displace the modifier in the pores of the modified multifunctional composite gel 9, and then dried by supercritical CO2 to obtain multifunctional composite aerogel 12. Step 5: As Figure 1 As shown, a multifunctional composite aerogel 12 is filled between an insulating conductor and a cable sheath to form a multifunctional composite aerogel layer 133. The cable sheath includes a shielding layer 134 and a protective layer 135. The insulating conductor includes a conductor 131 and an insulating outer layer 132 covering the outer surface of the conductor 131.

[0021] Preferably, in step one, the nickel-titanium wire 111 has a diameter of 100 μm, and the insulating layer 112 is a polyimide varnish. After the polyimide varnish is coated on the outer surface of the nickel-titanium wire 111, it is placed in an oven at 80°C for 1 hour to cure, at which time the insulating layer 112 is formed on the outer surface of the nickel-titanium wire 111.

[0022] Preferably, in step two, the preparation method of the phenolic resin prepolymer solution 2 containing thermochromic microcapsules 3 is as follows: resorcinol and formaldehyde are mixed in deionized water at a molar ratio of 1:2, and sodium carbonate is used as a catalyst to react at 60°C for 4 hours to obtain a phenolic resin prepolymer solution 2 with a solid content of 20%. In the phenolic resin prepolymer solution 2, thermochromic microcapsules 3 equivalent to 1 wt% of the solid mass of phenolic resin are added, and the mixture is stirred evenly to obtain the phenolic resin prepolymer solution 2 containing thermochromic microcapsules 3.

[0023] Preferably, in step two, the thermochromic microcapsule 3 is composed of an oil phase mixture (core material) and an aqueous phase mixture. The oil phase mixture is prepared by heating and melting 5 wt% crystal violet lactone, 25 wt% bisphenol A or octadecylphosphonic acid, and 70 wt% tetradecyl alcohol or hexadecyl alcohol, or a mixture thereof, at 85°C, and stirring to form a homogeneous liquid oil phase mixture. The aqueous phase mixture is prepared by adding deionized water and 10 wt% water-soluble polymer (such as gum arabic or styrene-maleic anhydride copolymer, as an emulsifier and stabilizer) to a beaker, stirring to dissolve and obtain the aqueous phase mixture. The oil phase mixture is slowly added to the aqueous phase mixture under high-speed shear (10,000 rpm) for 5-10 minutes to form a stable oil-in-water (O / W) emulsion. The droplet size of the emulsion determines the final microcapsule particle size (typically 5-20 μm). The pH of the emulsion is then adjusted to 3.5 using citric acid or sodium acetate solution. The mixture was kept in an acidic range of 4.5, and then 5 wt% melamine-formaldehyde prepolymer was slowly added. The mixture was stirred at a moderate speed and reacted at 60-70°C for 1 hour. Under acidic conditions and heating, the melamine-formaldehyde prepolymer gradually crosslinked and solidified, and its hydrophobicity increased. It precipitated from the aqueous phase mixture and deposited on the surface of the oil phase droplets, forming a transparent shell. The temperature was then gradually increased to 80-85°C, and the reaction was continued for 1-2 hours to completely solidify and harden the shell. After the reaction was completed, the mixture was cooled to room temperature, and the microcapsule product was collected by filtration. It was washed repeatedly with deionized water and ethanol until the filtrate was neutral and clear to remove all unreacted monomers and emulsifiers. Finally, the microcapsule product was vacuum dried at 40°C to obtain white thermochromic microcapsule powder.

[0024] Preferably, in step two, the preparation method of MXene / ethanol dispersion 4 is as follows: MXene aqueous dispersion (5 mg / mL) is filtered into a film by vacuum filtration, and then redispersed in anhydrous ethanol, and treated by ultrasonic treatment with a probe (300W, 2h) to obtain stable MXene / ethanol dispersion 4 (concentration ~2.5 mg / mL).

[0025] Preferably, in step two, the silica sol 5 is prepared by mixing tetraethyl orthosilicate, anhydrous ethanol, and deionized water in a molar ratio of 1:4:4, adding 0.1 mol HCl to adjust the pH to 3.0, and stirring at 40°C for 2 hours to obtain clear silica sol 5.

[0026] Preferably, in step three, the gelation and modification process is as follows: the polytetrafluoroethylene mold 8 containing the multifunctional composite sol 7 is placed in a 60°C forced-air drying oven and left to stand for 6 hours to complete the gelation process, resulting in a multifunctional composite wet gel. The multifunctional composite wet gel, along with the polytetrafluoroethylene mold 8, is then immersed in sufficient anhydrous ethanol and soaked at room temperature for 24 hours, during which the anhydrous ethanol is replaced 3 times to complete the aging process. Finally, the aged multifunctional composite wet gel is transferred to a 1wt% perfluorodecyltriethoxysilane / ethanol solution and soaked at 50°C for 48 hours (perfluorodecyltriethoxysilane is the modifier mentioned above) to complete the hydrophobic modification, resulting in the modified multifunctional composite gel 9.

[0027] Preferably, in step four, the supercritical CO2 drying process is as follows: the modified multifunctional composite gel 9 is placed in a supercritical drying vessel, liquid CO2 is introduced, and the temperature is maintained at 10℃ and 6 MPa for 2 hours. Then, the temperature is increased to 50℃ at 0.5℃ / min, and the pressure is increased to 12 MPa at 1 MPa / min. This condition is maintained for 3 hours. Finally, the pressure is released to atmospheric pressure at 50℃ at a very slow rate (≤0.1 MPa / min). After cooling to room temperature, the multifunctional composite aerogel 12 is obtained.

[0028] Preferably, in step five, the cable 13 comprises a conductor 131, an outer insulating layer 132, a multifunctional composite aerogel layer 133, a shielding layer 134, and a protective layer 135. The conductor 131 is made of multi-strand oxygen-free bare copper wire with a cross-sectional area of ​​1.5-4.0 mm², the outer insulating layer 132 is made of cross-linked polyethylene or silicone rubber with a thickness of 0.8-1.2 mm, the shielding layer 134 is made of tin-plated copper wire braided shield (density ≥85%), and the protective layer 135 is a fluoroplastic coating with a thickness of 0.5 mm.

[0029] The multifunctional composite aerogel layer 133 constructs an organic (phenolic resin)-inorganic (silica) interpenetrating network, utilizing the toughness of the phenolic resin to compensate for the brittleness of the silica, thus obtaining a flexible aerogel that is bendable and compression-resistant. Furthermore, based on the phenolic resin / silica dual network, a third-phase nanomaterial with special functions, MXene (Ti3C2T), is introduced. X An interpenetrating three-level network structure is constructed, utilizing the extremely high photothermal conversion efficiency of MXene for photothermal de-icing. Furthermore, pre-stretched nickel-titanium wire 111 serves as both a macroscopic heating and driving element; when energized, it rapidly heats up for de-icing; when the temperature exceeds its austenitic phase transformation initiation temperature (A... sWhen the cable 13 overheats, it attempts to return to its original state (contraction), generating a self-healing tightening force on the surrounding cracks. The introduction of thermochromic microcapsules 3 enables the intelligent early warning function of cable 13. Its color-changing temperature is 130℃. When cable 13 is locally overheated, an irreversible color change will occur, providing a visual early warning. This provides a valuable early warning time window for solving the technical problem of "how to achieve advanced and intuitive fire hazard early warning without power supply", realizing the leap from "passive protection" to "active early warning".

[0030] Introducing perfluorodecyltriethoxysilane for in-situ surface modification during the gel aging stage, rather than spraying it later, enables the aerogel skeleton to obtain durable and uniform superhydrophobic properties, thereby enhancing its waterproof and anti-icing properties.

Claims

1. A method for preparing a high-performance multifunctional cable, characterized in that: Includes the following steps: Step 1: Fix the nickel-titanium wire (111) on the pre-stretching fixture, stretch it at a uniform speed until a strain of 4% is generated, and then uniformly coat the surface with an insulating layer (112) to obtain a shape memory alloy wire (1). Tighten and fix the processed shape memory alloy wire (1) at the center of the inner cavity of the polytetrafluoroethylene mold (8). Step 2: Mix the phenolic resin prepolymer solution (2) containing thermochromic microcapsules (3), MXene / ethanol dispersion (4), and silica sol (5) in a mass ratio of 1:1:1 to obtain a mixed sol. Slowly add ammonia water (6) to precisely adjust the pH value of the mixed sol to 7.

5. After stirring, obtain a multifunctional composite sol (7). Step 3: Inject the multifunctional composite sol (7) into the polytetrafluoroethylene mold (8) with the shape memory alloy wire (1) fixed in place, seal the cover plate, and then perform gelation and modification to obtain the modified multifunctional composite gel (9). Step 4: The modified multifunctional composite gel (9) is soaked in anhydrous ethanol (10) and n-hexane (11) in sequence to displace the modifier in the pores of the modified multifunctional composite gel (9), and then dried with supercritical CO2 to obtain multifunctional composite aerogel (12). Step 5: Fill the space between the conductor with insulation layer and the cable sheath with multifunctional composite aerogel (12) to form a multifunctional composite aerogel layer (133).

2. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step one, the diameter of the nickel-titanium wire (111) is 100μm, and the insulating layer (112) is polyimide varnish. After the polyimide varnish is coated on the outer surface of the nickel-titanium wire (111), it is placed in an 80℃ oven for 1 hour to cure, and an insulating layer (112) will be formed on the outer surface of the nickel-titanium wire (111).

3. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step two, the preparation method of the phenolic resin prepolymer solution (2) containing thermochromic microcapsules (3) is as follows: resorcinol and formaldehyde are mixed in deionized water at a molar ratio of 1:2, and sodium carbonate is used as a catalyst to react at 60°C for 4 hours to obtain a phenolic resin prepolymer solution (2) with a solid content of 20%. In the phenolic resin prepolymer solution (2), thermochromic microcapsules (3) equivalent to 1 wt% of the solid mass of phenolic resin are added, and the mixture is stirred evenly to obtain the phenolic resin prepolymer solution (2) containing thermochromic microcapsules (3).

4. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step two, the thermochromic microcapsules (3) consist of an oil phase mixture and an aqueous phase mixture. The oil phase mixture is prepared by heating and melting 5 wt% crystal violet lactone, 25 wt% bisphenol A or octadecylphosphonic acid, and 70 wt% tetradecyl alcohol or hexadecyl alcohol or a mixture thereof at 85°C, and stirring to form a homogeneous liquid oil phase mixture. The aqueous phase mixture is prepared by adding deionized water and 10 wt% water-soluble polymer to a beaker, stirring and dissolving to obtain an aqueous phase mixture. The oil phase mixture is added to the aqueous phase mixture under shear at 10,000 rpm, and sheared continuously for 5-10 minutes to form a stable oil-in-water emulsion. The pH of the emulsion is adjusted to 3.5 using citric acid or sodium acetate solution. 4.5% acid range, slowly add 5wt% melamine-formaldehyde prepolymer, stir, react at 60-70°C for 1 hour, melamine-formaldehyde prepolymer gradually crosslinks and solidifies and precipitates from the aqueous phase mixture and deposits on the surface of the oil phase droplets to form a transparent shell. Then gradually raise the temperature to 80-85°C and continue to react for 1-2 hours to make the shell completely solidify and harden. After the reaction is completed, cool to room temperature, filter and collect the microcapsule product, wash repeatedly with deionized water and ethanol until the filtrate is neutral and clear, vacuum dry the microcapsule product at 40°C to obtain white thermochromic microcapsule (3) powder.

5. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step two, the preparation method of MXene / ethanol dispersion (4) is as follows: the MXene aqueous dispersion is filtered into a film by vacuum filtration, and then redispersed in anhydrous ethanol. After ultrasonic treatment by probe, a stable MXene / ethanol dispersion (4) is obtained.

6. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step two, the preparation method of silica sol (5) is as follows: tetraethyl orthosilicate, anhydrous ethanol and deionized water are mixed in a molar ratio of 1:4:4, HCl is added dropwise to adjust the pH to 3.0, and the mixture is stirred at 40°C for 2 hours to obtain clear silica sol (5).

7. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step three, the gelation and modification process is as follows: the polytetrafluoroethylene mold (8) injected with multifunctional composite sol (7) is placed in a 60°C forced-air drying oven and left to stand for 6 hours to complete the gelation process and obtain multifunctional composite wet gel. The multifunctional composite wet gel, together with the polytetrafluoroethylene mold (8), is then immersed in sufficient anhydrous ethanol and soaked at room temperature for 24 hours, during which the anhydrous ethanol is replaced 3 times to complete the aging process. Finally, the aged multifunctional composite wet gel is transferred to perfluorodecyltriethoxysilane / ethanol solution and soaked at 50°C for 48 hours to complete the hydrophobic modification.

8. The method for preparing a high-performance multifunctional cable according to claim 1, characterized in that: In step four: the supercritical CO2 drying process is as follows: the modified multifunctional composite gel (9) is placed in a supercritical drying vessel, liquid CO2 is introduced, and it is kept at 10℃ and 6 MPa for 2 hours. Then, the temperature is increased to 50℃ at 0.5℃ / min, and the pressure is increased to 12MPa at 1 MPa / min. It is kept under this condition for 3 hours. Finally, at 50℃, the pressure is released to atmospheric pressure at a rate of ≤0.1 MPa / min.

9. A high-performance, multi-functional cable, characterized in that: It is prepared by any one of the preparation methods of high-performance multifunctional cable according to claims 1 to 8.

Citation Information

Patent Citations

  • Efficient flame retardant cable sheath material

    CN103992580A

  • Shape memory aerogel material and preparation method thereof

    CN108212032A

  • Phase change microcapsule composite aluminum trioxide-silicon dioxide aerogel and preparation method thereof

    CN112390570A

  • Communication cable sheath material and preparation process thereof

    CN119400494A

  • High-toughness halogen-free flame-retardant crosslinked cable and preparation method thereof

    CN119842130A